Pengaruh Audit Forensik Terhadap Pencegahan Dan Pengungkapan Fraud - Anggi Sari Tambunan; Tuti Meutia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the effect of forensic audits on preventing and disclosing fraud. In the context of rapid world development and increasingly advanced technology, fraud has become a serious problem that can harm companies both in government and the private sector. Fraud is carried out with various motives, such as looting of assets, corruption, and manipulation of financial reports. One way to reduce the opportunity for fraud to occur is to implement adequate internal controls. Forensic audits have an important role in providing evidence that can be used in legal processes and in preventing and exposing fraud. This research uses a qualitative approach and literature review to support findings regarding the influence of forensic audits on fraud prevention and disclosure